Erosion corrosion and tribological behavior of TIG torch composite layers - Maleque, Md. Abdul (Research Management Centre, International Islamic University Malaysia, 2016)
Advances in technological development in aerospace, automotive, power plant, chemical plant and marine industries has given rise to constantly increasing demands for material surfaces that can withstand mild to severe tribological conditions. As a result of this, several surface coating techniques have been developed to embed ceramic particles in the near surface layer of engineering materials in order to enhance their hardness and wear performance. Among the coating techniques, tungsten inert gas (TIG) torch melting technique is currently gaining wide acceptance in surface coating of engineering part component for tribological use. In this study, powder preplacement and tungsten inert gas (TIG) torch melting technique have been successfully employed to generate a number of tribological hard composite coatings on AISI 4340 low alloy steels (LAS) and commercial purity titanium (CP-Ti) alloys. The composite coatings have been formed from the use of ceramic materials such titanium carbides, Fe, graphite (C), silicon (Si), hexagonal boron nitride powders (hBN) and electroless nickel-coated hBN (Ni-P-hBN). Specifically, the coatings were processed by precoating or preplacing of Fe-C-Si powders on the surface of CP-Ti and TiC-based (TiC or TiC/hBN or TiC/Ni-P-hBN) powder mixture on AISI4340 LAS surface, and then melted under the TIG torch arc to generate single-phase and multi-phase (ternary alloys and hybrid) composite layers or coatings using a controlled TIG melting conditions. The cross sectional microstructures and surface hardness of the developed coatings were analyzed using SEM, XRD, EDX and Vickers microhardness tester. Moreover, the friction and wear behaviors of the composite coatings both at room temperature and 600 OC were evaluated using ball-on-disc tribometer. The results generally indicated that TIG-embedded surface coating showed surface characteristics (topography, hardness and wear behaviors) that are controlled by the powder composition and content, TIG process parameters and microstrural evolution. Based on the findings, it can be concluded that TIG torch melting technique is a versatile and economic process for the formation of composite coating layer on the steel and Ti-alloy in order to widen their applications for aggressive tribological environment involving dry sliding and high temperature.